Designers' guide to EN 1997-1 : Eurocode 7. - Frank, R. (Designers' guides to the Eurocodes., 2004)
This book describes and explains the many features of ground engineering that require special design attention to ensure safety and adequate performance. It is useful for civil and structural engineers code-drafting committees; clients; structural-design students and public authorities.